Amentoflavone Inhibits Osteoclastogenesis and Wear Debris-Induced Osteolysis via Suppressing NF-κB and MAPKs Signaling Pathways - Zhang, Zhen; Zhao, Shuai; Li, Xiaolei; Zhuo, Xiaoqi; Zhang, Wu; Nie, Qian; Wang, Shuguang; Yan, Lianqi; Sun, Yu (Planta Medica, 2018)
Wear debris-induced osteolysis is one of the major reasons for subsequent aseptic loosening after cementless hip arthroplasty. Increasing evidence suggests that receptor activator of nuclear factor kappa-B (NF-κB) ligand-mediated osteoclastogenesis and osteolysis are responsible for wear debris-induced aseptic loosening. In the present study, we explored the effect of amentoflavone (AMF) on inhibiting osteoclast generation and wear debris-induced osteolysis in vitro and in vivo. Twenty-four male C57BL/J6 mice were randomly divided into four groups: a sham group and groups with titanium wear debris treatment followed by intraperitoneal injection of various concentrations of AMF (0, 20, and 40 mg/kg/day). The micro computed tomography scanning and histological analysis were performed. Bone marrow-derived macrophages were cultured to investigate the effect of AMF on osteoclast generation and function. The results showed that AMF suppressed osteoclastogenesis, F-actin ring formation, and bone absorption without cytotoxicity. AMF prevented titanium wear debris-induced osteolysis in mice. AMF suppressed the relative proteins of NF-κB and mitogen-activated protein kinase (MAPKs) signaling pathways. Thus, the present study suggests that AMF derived from plants could inhibit osteoclastogenesis and titanium wear debris-induced osteolysis via suppressing NF-κB and MAPKs signaling pathways.
Keywords: amentoflavone; osteoclastogenesis; osteolysis; RANKL; MAPKs; NF-κB